Research Notes. Stakeholders and Corporate Boards: Institutional Influences on Board Composition and Structure - Luoma, Patrice; Goodstein, Jerry (Academy of Management Journal, 1999)
This study examined the relationships between institutional influences and stakeholder representation on boards of directors. Data from 224 companies over the period 1984–94 were employed. Results indicate that variations in legal environments, industry regulation, and firm size are associated with stakeholder representation on boards but do not influence stakeholder representation on key board committees. Legal environments and firm size are associated with the adoption of stakeholder-oriented board committees.